Suture Repair versus Arrow Repair for Symptomatic Meniscus Tears of the Knee: A Systematic Review - Ayeni, Olufemi; Peterson, Devin; Chan, Kevin; Javidan, Ashkan; Gandhi, Rajiv (The Journal of Knee Surgery, 2012)
A healthy meniscus is important for normal function of the knee. Numerous studies support that the repair of a torn meniscus is important to prevent degenerative changes in the knee. The ability to repair torn menisci is based on several factors including location, tear orientation, chronicity, and concomitant ligamentous knee injuries. In this systematic review, meniscal repair technology is evaluated. Specifically, the retear rates are compared between the arrow repair and the suture repair techniques. After searching three databases (PubMed, Cochrane Central Register of Controlled Trials, and Embase) and reviewing annual meeting abstracts from the American Orthopaedic Society for Sports Medicine (2005 to 2010), four studies (two observational and two randomized controlled trials) were selected for this systematic review. Due to the limited study number and variability between studies (study design, sample population, outcome measures, and surgical technique), a meta-analysis was not performed. The overall quality of the literature was poor and thus conclusions are limited. No clear superiority of one technique was determined by this review.
Keywords: meniscus; meniscal repair